Peran Kampung KB Sendangsari untuk Mencegah Stunting - Rahmisutar, Rahmisutar; Astuti, Eka Zuni Lusi (UI Scholars Hub, 2021)
The 2020-2024 RPJMN places stunting as a priority issue in health development. The 2019 Study on the Nutritional Status of Toddlers in Indonesia (SSGBI) which was integrated with the March 2019 Susenas showed that the prevalence of stunting in Indonesia in 2019 was still high, at 26.67%. One of the efforts taken by the government is to focus the Quality Family Village Program (KB) on the issue of stunting prevention. KB Villages can mobilize participation and synergy of various institutions in the community to play a role in preventing stunting. This paper discusses the role of the Sendangsari KB Village in empowering the community for stunting prevention. The data were collected and analyzed using qualitative research methods with an exploratory approach. The results of this study indicate that the prevention of stunting by the Sendangsari KB Village is carried out in two ways. First, implementing various stunting prevention activities, such as monitoring the growth of toddlers through health screening and supplementary feeding. Second, encourage collaboration across activity groups, such as BKB Kenanga, BKR Tunas Harapan, PIK-R Mekar Asri, UPPKA Mukti Migunani, KWT Dhuawar, Pokdakan Beliksari and Pokdakan Gondangsari, Posyandu Kenanga, and Posbindu Kenanga, so that they can play a role in stunting prevention. In addition, external actors from the local government, related agencies and academics also contribute to facilitating Sendangsari KB Village through various assistance and training to improve community skills.